The Influence Of Mathematical Critical Thinking Skills: Motivation, Learning Model, And Learning Style - Khairunnisa Siregar (ISNU Sumatera Utara, 2024)
This study aims to examine the influence of motivation, learning models, and learning styles on students' mathematical critical thinking skills. Critical thinking is an essential skill in mathematics, as it helps students solve complex problems by applying logical reasoning and analysis. The importance of motivation, appropriate learning models, and personalized learning styles is crucial to fostering critical thinking abilities in students. The research uses a normative juridical approach, focusing on the relationship between educational norms and the application of different learning strategies. Data is collected through literature review, analyzing previous studies, educational policies, and theoretical frameworks related to motivation, learning models, and learning styles. The descriptive qualitative method was employed to interpret and analyze the data. The results reveal that motivation plays a significant role in enhancing critical thinking skills. Students with higher motivation levels tend to perform better in mathematical reasoning and problem-solving. Moreover, the choice of learning models impacts the development of students' critical thinking skills. Problem-based learning models, for instance, engage students in real-world problem-solving activities, thereby enhancing their mathematical reasoning abilities. Furthermore, accommodating students’ individual learning styles is essential for optimizing their critical thinking potential. Visual learners, for example, may excel in analyzing diagrams and charts, while auditory learners might benefit from verbal explanations. In conclusion, the findings suggest that motivation, learning models, and learning styles are all significant factors that influence students' mathematical critical thinking skills. Educators should focus on creating an engaging learning environment that fosters motivation, employs diverse learning models, and adapts to different learning styles to enhance students' critical thinking abilities in mathematics. These efforts will lead to improved academic performance and better problem-solving skills among students.